2023
DOI: 10.21203/rs.3.rs-2993839/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

It starts at home: consumer acceptance of battery storage and response to prosumer models

Abstract: The deployment of battery storage is crucial to decarbonizing the energy sector and mitigating climate change. The study examines the antecedents of battery storage acceptance and perceptions of prosumer and leasing models. An online survey was conducted with 609 homeowners in Australia, a mature renewable energy market. A two-step econometric model was used to analyze the data. The result shows that an environmental self-identity, subjective norms, the independence motive, technical interest, load-shifting in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Additionally, individuals with higher income levels may be more inclined to consider long-term benefits and environmental impact, even if the initial investment is higher. The research showed that home ownership, unwillingness to sacrifice personal comforts to save electricity, being pro-energy efficiency, and income are positively related to rooftop solar installation (McCarthy and Liu, 2023). Moreover, the fraction of customers who adopt home rooftop solar power systems in any year is based solely on the money saved by doing so in that year (Cai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, individuals with higher income levels may be more inclined to consider long-term benefits and environmental impact, even if the initial investment is higher. The research showed that home ownership, unwillingness to sacrifice personal comforts to save electricity, being pro-energy efficiency, and income are positively related to rooftop solar installation (McCarthy and Liu, 2023). Moreover, the fraction of customers who adopt home rooftop solar power systems in any year is based solely on the money saved by doing so in that year (Cai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%